Influencia de la motivación en los equipos de trabajo para el desarrollo de la empresa Inversiones y Servicios Pranex E.I.R.L. - Vargas Paitan, Araceli Del Pilar (2012)
This paper has been prepared in order to identify as influencing motivation in teams of investment and Services Company Pranex E.I.R.L, as currenthy is developing a plan of motivation to their team sempirically as bonds, incentives, prizes, awards and are not consistent with objectives implemented. This thesis we will announce how motivation affects each member of tha Investment Company equipment and E.I.R.L Pranex Servicesln addition, identifying weaknesses in the infringing work teams and how they can increase their productivity by working towards achieving a common goal that can benefit members of the Company to establish a truly sustainable in the telecommunications sector. I conclude that, at the end of this research, it will yield that contribute to increased productivity and satisfactions of staff for motivation injected into the investment and Services Company E.I.R.L Pranex.